Effect of three-dimensional print angle on integrity of interim crowns: A systematic review - Lins, Laura Buarque Caminha; Leão, Rafaella de Souza; Pellizzer, Eduardo Piza; Vasconcelos, Belmiro Cavalcanti do Egito [UNESP]; de Moraes, Sandra Lúcia Dantas (Elsevier, 2024)
Statement of problem: Three-dimensional printing is a rapid and cost-effective method that eliminates material waste during the manufacture of indirect restorations. Parameters such as print angle significantly affect the physical properties of the printed material. Several manufacturers suggest using an angle of 45 degrees to perform printing; however, different angles have been used, and the optimum parameters are unclear. Purpose: The purpose of this systematic review was to compare the 45-degree print angle with other protocols and evaluate the effect of print angle on the physical and mechanical material properties. Material and methods: Two researchers independently searched for relevant studies published up to June 2023 in the PubMed/MEDLINE, Scopus, Web of Science, and Lilacs electronic databases. The population, intervention, comparison, outcome (PICO) question was: “Does the 45-degree print angle promote better physical characteristics for 3-dimensionally printed interim crowns?” Studies that compared the properties of the different print angles of interim crowns were analyzed. Results: Ten in vitro studies were selected for qualitative analysis. When evaluating marginal and internal fits, most studies selected the 45-degree angle, resulting in less discrepancy. The results of flexural strength analysis showed a high level of heterogeneity. The 0-degree print angle yielded better results in 3 studies, followed by the 90-degree print angle in 2 studies. The 45-degree angle yielded the highest fracture resistance value in 1 study and similar results to those of the control group (milled PMMA) in another study. Conclusions: The marginal and internal adaptation and resistance to flexure of printed interim crowns are satisfactory when a 45-degree print angle is used.